(3JQJjH GdeOGQc hJbQjH GdSGdc deYQag CYdGe ePgH eGdcs - (3YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s ((3CHh HcQ Hf CMeO Hf eMeO Hf eMeO GdWhNi s)
(3ChdgG (B:s
(3hHYO adeG JcQQJ GdCUMGH dEeVGA eG cGfJ Gdfjg GYJbOJg hJHjV eGZOJ Gdgeg bO ShOJg ef cJGH LGO dCSeGA GdeGdcjI hCYjGfge hCYdGege s
(3BNQgG (B:s
(3JQLeI CHj WGdH bGVi GdbjQhGf jJdhg ai GdKGfi JQLeI CHj WGdH bGVi GdbjQhGf jJdhg ai GdKGfi JQLeI YjSi Hf eScjf GdGaQjbjf s
(3GdLRA GdCNjQ ef GdeOGQc jHJOF ai JQLeI YjS Hf eScjfs
(3GfXQ Qbe (B" 174" (3JQGjNs
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs